Politische Gewalt in Kolumbien Die Violencia in Tolima, 1946-1964 - Rehm, Lukas (Historamericana, 2022)
The civil war in the middle of the 20th century, the Violencia, characterizes Colombia to this day. Lukas Rehm examines from a cultural-historical perspective how the contrast between liberals and conservatives was created. He also analyzes the civil war from the perspective of the Tolino Department.